Cell, cell stack device, module, and module housing device
Patent Information
- Application Number
- JP2023044959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-24
- Filing Date
- 2023-03-22
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-04-23
Smart Images

Figure 0007645920000001 
Figure 0007645920000002 
Figure 0007645920000003
Abstract
Description
[Technical field]
[0001] This disclosure , Se The present invention relates to a cell stack device, a module, and a module housing device. [Background technology]
[0002] In recent years, fuel cell devices used as next-generation energy sources use cells in which, for example, a fuel electrode layer, a solid electrolyte layer, and an air electrode layer are laminated on a porous support. Ceramic materials, metal materials, and the like are used for the support. Metal materials such as ferritic stainless steel having high heat resistance and corrosion resistance are used for the metal support, and metal sintered bodies obtained by sintering powder of metal materials, or metal plates having through holes are used. For example, Patent Document 1 discloses a SOFC (Solid Oxide Fuel Cell) in which a porous metal containing Fe and Cr is used as the support. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-115506 A Summary of the Invention
[0004] The conductive member of the present disclosure includes a metal body containing Cr and a film containing Cr2O3 located on a surface of the metal body. The film includes first conductive particles different from Cr2O3.
[0005] The cell of the present disclosure includes the conductive member described above, and an element portion disposed on the first surface and having a first electrode layer, a solid electrolyte layer located on the first electrode layer, and a second electrode layer located on the solid electrolyte layer, and the membrane is located between the first surface and the first electrode layer.
[0006] The cell stack device of the present disclosure includes a cell stack in which the above-described cells are arranged.
[0007] The module of the present disclosure includes a container and the above-mentioned cell stack device housed in the container.
[0008] The module housing device of the present disclosure comprises an outer case, and the above-mentioned module and accessories for operating the module housed within the outer case. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a cross section of a cell. [Diagram 2] 2 is a cross-sectional view showing an example in which the dashed line portion in FIG. 1 is enlarged. [Diagram 3] 2 is a cross-sectional view showing an example in which the dashed line portion in FIG. 1 is enlarged. [Figure 4] FIG. 2 is a cross-sectional view showing an example of a cross section of a cell. [Diagram 5] 2 is a cross-sectional view showing an example in which the dashed line portion in FIG. 1 is enlarged. [Figure 6] 2 is a cross-sectional view showing an example in which the dashed line portion in FIG. 1 is enlarged. [Figure 7] 2 is a cross-sectional view showing an example in which the dashed line portion in FIG. 1 is enlarged. [Figure 8] 2 is a cross-sectional view of an example cell and a plan view of a first surface of a metal plate. FIG. [Figure 9] 2 is a cross-sectional view of an example cell and a plan view of a first surface of a metal plate. FIG. [Figure 10] 2 is a cross-sectional view of an example cell and a plan view of a first surface of a metal plate. FIG. [Figure 11] FIG. 2 is a side view that illustrates a schematic diagram of an example of a cell stack device. [Figure 12] 12 is an enlarged cross-sectional view of a portion of the cell stack device shown in FIG. 11 surrounded by a dashed line. [Figure 13] FIG. 2 is an external perspective view showing an example of a module. [Figure 14] FIG. 1 is a perspective view showing an example of a module receiving device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (cell) 1 shows an example of a cross section of a cell having a metal support. The cell 1 includes a metal support having a metal plate 2 having a pair of opposing first and second surfaces 2a and 2b, and a flow path member 8, and an element section 6. The element section 6 is disposed on the first surface of the metal plate 2, and includes a first electrode layer 3, a solid electrolyte layer 4, and a second electrode layer 5. The first electrode layer 3 is disposed on the first surface of the metal plate 2, the solid electrolyte layer 4 is disposed on the first electrode layer 3, and the second electrode layer 5 is disposed on the solid electrolyte layer 4.
[0011] The metal support has a gas flow path 7 formed by a flow path member 8 and a second surface 2b opposite to a first surface 2a on which the element portion 6 of the metal plate 2 is arranged.
[0012] The metal plate 2 has gas permeability that allows the gas flowing through the gas flow passage 7 to pass through to the first electrode layer 3. The flow passage member 8 has gas barrier properties that prevent gas from passing between the gas flow passage 7 and the outside of the cell 1, that is, prevents mixing of the fuel gas with an oxygen-containing gas such as air. In the example of Fig. 1, the gas flow passage 7 is formed by the metal plate 2 and the flow passage member 8 having a U-shaped cross section.
[0013] The solid electrolyte layer 4 may cover the entire surface of the first electrode layer 3 that is not in contact with the metal plate 2. The solid electrolyte layer 4 and the flow path member 8 may form a cylindrical body. In addition, the surface of the first electrode layer 3 that is not in contact with the metal plate 2 or the solid electrolyte layer 4 may be covered with another material that does not have gas permeability.
[0014] In the following, the same reference numerals will be used for the same components in other figures. In each figure, for ease of explanation, the thickness direction of each layer is enlarged, and the actual thickness of each layer is very small compared to the size of the cell 1. In addition, to clarify the arrangement of each component constituting the cell 1, the xyz coordinate axes are shown.
[0015] In the following description, unless otherwise specified, the first electrode layer 3 located between the metal plate 2 and the solid electrolyte layer 4 is the fuel electrode, and the second electrode layer 5 located on the solid electrolyte layer 4 is the air electrode. A fuel gas such as a hydrogen-containing gas is supplied to the gas flow channel 7, i.e., the second surface 2b side, which is the lower side of the metal plate 2 shown in FIG. 1, and an oxygen-containing gas such as air is supplied to the upper side of the second electrode layer 5, which is the air electrode. The first electrode layer 3 may be the air electrode, and the second electrode layer 5 may be the fuel electrode. In this case, an oxygen-containing gas such as air is supplied to the lower side of the metal plate 2 of the cell 1 shown in FIG. 1, and a fuel gas such as a hydrogen-containing gas is supplied to the upper side of the second electrode layer 5, which is the fuel electrode.
[0016] The cell 1 may be, for example, a solid oxide cell 1. The solid oxide cell 1 has high power generation efficiency as a fuel cell, and allows the entire power generation device to be made smaller. In addition, the solid oxide cell 1 can perform load following operation, and can follow the fluctuating load required, for example, in a household fuel cell.
[0017] The fuel electrode may be made of a material generally known as a fuel electrode. The fuel electrode may include a porous conductive ceramic, such as stabilized zirconia, and Ni and / or NiO. The stabilized zirconia is, for example, ZrO2 in which magnesium (Mg), calcium (Ca) or a rare earth element is solid-dissolved, and also includes partially stabilized zirconia. The rare earth element in the present disclosure includes yttrium (Y).
[0018] The solid electrolyte layer 4 is an electrolyte that bridges the charge between the first electrode layer 3 and the second electrode layer 5. The solid electrolyte layer 4 has gas barrier properties so that the fuel gas and oxygen-containing gas such as air do not mix. The material of the solid electrolyte layer 4 is not particularly limited as long as it is an electrolyte having gas barrier properties, and may be, for example, ZrO2 in which 3 mol % to 15 mol % of a rare earth element oxide is dissolved.
[0019] The air electrode may be made of a material generally used for air electrodes. The air electrode may be made of, for example, conductive ceramics of a so-called ABO3 type perovskite oxide. The air electrode has gas permeability. The open porosity of the air electrode may be 20% or more, particularly in the range of 30% to 50%.
[0020] The metal plate 2 has electrical conductivity. The electrical conductivity of the metal plate 2 allows it to collect electricity generated in the element portion 6. The electrical conductivity of the metal plate 2 may be, for example, 3.0 S / m or more, particularly 4.4 S / m or more.
[0021] Furthermore, the metal plate 2 is capable of passing gas between the first surface 2a and the second surface 2b. That is, the metal plate 2 has gas permeability between the first surface 2a and the second surface 2b. The gas permeability of the metal plate 2 allows the fuel gas supplied to the gas flow passage 7 to reach the first electrode layer 3, which is the fuel electrode.
[0022] 2 and 3 are cross-sectional views each showing an enlarged broken line portion in FIG. 1. The metal plate 2 may be a flat porous body having an open porosity of, for example, 30% or more, particularly in the range of 35% to 50%. The metal plate 2 may also be a dense plate having a plurality of through holes 10 penetrating the metal plate 2 in the thickness direction, as shown in FIG. 3. The through holes 10 may have a diameter of, for example, 0.01 mm or more and 1.0 mm or less in a cross section perpendicular to the thickness direction of the metal plate 2. When the metal plate 2 has such an open porosity or through holes 10, the fuel gas supplied to the gas flow passage 7 can reach the first electrode layer 3, which is the fuel electrode.
[0023] The dense metal plate 2 has a smaller surface area and higher corrosion resistance than the porous metal plate 2. In addition, the dense metal plate 2 has a smaller surface area, so that the oxide film formed on the surface, i.e., the oxide content, is smaller, and the dense metal plate 2 has higher electrical conductivity.
[0024] The shape of the metal plate 2 may be a flat plate having a pair of opposing flat surfaces, a first surface 2a and a second surface 2b, as shown in Figure 1 and Figure 2. The shape of the metal plate 2 may be a curved plate having a pair of opposing curved surfaces, a first surface 2a and a second surface 2b, as shown in Figure 4. The thickness of the metal plate 2 may be, for example, 100 µm or more and 1 mm or less.
[0025] The material of the metal plate 2 may be, for example, a conductive material such as a heat-resistant alloy. The metal plate 2 contains Cr, and may contain, for example, 4 atomic % to 30 atomic % of chromium (Cr) with respect to the entire alloy. The alloy containing Cr may be a nickel-chromium alloy, an iron-chromium alloy, and austenitic, ferritic, and austenitic-ferritic stainless steel, etc. Furthermore, the metal plate 2 may contain manganese (Mn) and aluminum (Al) as elements other than Cr.
[0026] The metal plate 2 and the first electrode layer 3 are often joined by heat treatment in air or a nitrogen atmosphere. This is because heat treatment in a reducing atmosphere or vacuum tends to promote sintering of the first electrode layer 3 or the second electrode layer 5, making it difficult to make them porous. During this heat treatment, the surface of the alloy containing Cr is oxidized, and a passive film of chromium oxide (Cr2O3) is formed on the surface of the alloy. This passive film gives the metal plate 2 high corrosion resistance. However, Cr2O3 has low electrical conductivity, which increases the electrical resistance between the metal plate 2 and the first electrode layer 3, such as the fuel electrode.
[0027] As shown in Figs. 2 and 3, the cell 1 of the present disclosure has a first intermediate layer 9 between the first surface 2a of the metal plate 2 and the first electrode layer 3, the first intermediate layer 9 containing chromium oxide (Cr2O3) and a first conductive particle different from Cr2O3. The first intermediate layer 9 has electrical conductivity. As shown in Fig. 2, the first intermediate layer 9 may be a porous layer having an open porosity of, for example, 30% or more, particularly in the range of 35% to 50%. Also, as shown in Fig. 3, the first intermediate layer 9 may have a plurality of through holes 10 penetrating the first intermediate layer 9 in the thickness direction. The first intermediate layer 9 having a plurality of through holes 10 may be a dense layer. The first intermediate layer 9 is sandwiched between the first surface 2a of the metal plate 2 and the first electrode layer 3. When the metal plate 2 has the through holes 10, the through holes 10 also penetrate the first intermediate layer 9. The average thickness t1 of the first intermediate layer 9 may be, for example, 0.5 µm or more and 20 µm or less.
[0028] The first intermediate layer 9 contains chromium oxide (Cr2O3), which can increase the durability of the metal plate 2 even in a high-temperature reaction atmosphere. 10 Since the first intermediate layer 9 is an insulator having an electrical resistivity of about Ω·m, when the first intermediate layer 9 contains only Cr2O3, the electrical resistance between the metal plate 2 and the first electrode layer 3 increases, and it becomes difficult for the metal plate 2 to collect electricity generated in the element unit 6. When the first intermediate layer 9 contains Cr2O3 and further contains first conductive particles different from Cr2O3, the conductivity of the first intermediate layer 9 increases, and it becomes easier for the metal plate 2 to collect electricity generated in the element unit 6 through the first conductive particles different from Cr2O3. As a result, the power generation efficiency of the cell 1 can be improved. The first conductive particles different from Cr2O3 are particles having an electrical resistivity of about 10 Ω·m or less.
[0029] The particle size of the first conductive particles different from Cr2O3 is smaller than the thickness t1 of the first intermediate layer 9. The particle size of the first conductive particles is, for example, smaller than 0.5 μm. Hereinafter, the first conductive particles different from Cr2O3 may be simply referred to as the first conductive particles.
[0030] The electrical resistance of Cr2O3 tends to decrease when other elements such as Ti and Mn are dissolved in it. However, the movement of electrons in Cr2O3 basically occurs when electrons trapped in Cr atoms hop between atoms. The amount of electrons that move by hopping is very small compared to the amount of free electrons that flow in metals. Therefore, even if other elements are dissolved in Cr2O3, it does not exhibit the same electrical conductivity as metals. Furthermore, the electrical resistance of Cr2O3 varies depending on the type and amount of the dissolved elements, as well as the surrounding atmosphere, such as the partial pressure of oxygen, and stable characteristics cannot be obtained.
[0031] The first intermediate layer 9 of the present disclosure contains first conductive particles different from Cr2O3. When the first conductive particles different from Cr2O3 are dispersed in the first intermediate layer 9, the electrical resistance is reduced due to the conductivity of the first conductive particles themselves, and a current path is formed in the first intermediate layer 9 due to the contact between the first conductive particles, making it easier for the current to flow. Furthermore, even if the first conductive particles are not in contact with each other, it is considered that the electric field strength applied to the Cr2O3 between the first conductive particles is increased, making it easier for the current to flow. Therefore, the electrical resistance of the first intermediate layer 9 as a whole is smaller and the conductivity is higher when the first conductive particles are dispersed than when other elements are dissolved in Cr2O3. In particular, the conductivity of the entire first intermediate layer 9 can be further increased by using a metal having free electrons as the first conductive particles. In the first intermediate layer 9, other elements such as Ti, Mn, etc. may be dissolved in the Cr2O3 in the first intermediate layer 9.
[0032] The first conductive particles may be covered with the first intermediate layer 9. That is, the first conductive particles may be inside the first intermediate layer 9 and not exposed from the first intermediate layer 9. When the first conductive particles are covered with the first intermediate layer 9, that is, with Cr2O3 in the first intermediate layer, even if the conductivity of the first conductive particles varies due to differences in the atmosphere in contact with the first conductive particles, the influence of differences in the atmosphere around the first intermediate layer 9 on the first conductive particles is reduced. As a result, the conductivity of the first conductive particles is less likely to vary. The difference in the atmosphere is, for example, a difference in the concentration of the fuel gas in contact with the first intermediate layer 9.
[0033] The cell in which the metal plate 2 and the first electrode layer 3 are directly bonded has a lower electrical resistance between the metal plate 2 and the first electrode layer 3 than the cell 1 having a passive oxide layer or a first intermediate layer 9 between the metal plate 2 and the first electrode layer 3. However, since the metal plate 2 of such a cell does not have a passive layer, there is a concern that the corrosion resistance may be reduced.
[0034] The first intermediate layer 9 may contain, for example, 50 mol % or more and 95 mol % or less of Cr2O3 and, for example, more than 5 mol % and less than 50 mol % of the first conductive particles, calculated as oxides, relative to the total amount of elements contained in the first intermediate layer 9 calculated as oxides. The first intermediate layer 9 may also contain, for example, approximately 3 vol % or more and 40 vol % or less of the first conductive particles. A method for measuring the composition of the first intermediate layer 9 will be described later.
[0035] The first intermediate layer 9 may contain at least one of manganese (Mn) and aluminum (Al) in addition to Cr2O3 and the first conductive particles. For example, when the first intermediate layer 9 contains Mn, Mn may form MnCr2O4, which is a spinel crystal that is a composite oxide of Cr and Mn. Mn and Al may be contained in the metal plate 2.
[0036] The first conductive particles may be, for example, particles of a metal or alloy, particles of a conductive oxide, etc. The first conductive particles may include, for example, a metal or alloy, such as Ni, Cu, Co, Fe, and Ti. Metals or alloys, such as Ni, Cu, Co, Fe, and Ti, are 10 -6 It has an electrical resistivity of about Ω·m or less and exhibits high conductivity. The first conductive particles may also contain lanthanum chromite-based perovskite oxides (LaCrO3-based oxides) and lanthanum strontium titanium-based perovskite oxides (LaSrTiO3-based oxides). These perovskite oxides have an electrical resistivity of about 10 Ω·m or less and exhibit electrical conductivity, and are not reduced or oxidized even when in contact with fuel gases such as hydrogen-containing gases and oxygen-containing gases such as air. These metals or alloys and perovskite oxides are stable even at high temperatures and have high electrical conductivity, making it easier for the metal plate 2 to collect electricity generated by the element unit 6.
[0037] In particular, metallic Ni not only has high electrical conductivity, but also has a conductivity that is less likely to vary depending on the atmosphere. Therefore, metallic Ni can maintain high electrical conductivity even in a high-temperature reaction atmosphere. Therefore, metallic Ni can maintain stable electrical conductivity even if the surrounding atmosphere, for example, the concentration of fuel gas, varies. In addition, Ni is contained in the first electrode layer 3, which is the fuel electrode, and the first intermediate layer 9 contains first conductive particles containing Ni, thereby improving the bonding between the first intermediate layer 9 and the first electrode layer 3.
[0038] As shown in FIG. 5, the cell 1 may further have a porous second intermediate layer 11 between the first intermediate layer 9 and the first electrode layer 3. The second intermediate layer 11 also has gas permeability and electrical conductivity. The second intermediate layer 11 may have an open porosity of, for example, 30% or more, particularly 35% or more and 50% or less. When the metal plate 2 has a through hole 10, the through hole 10 may penetrate the second intermediate layer 11 in the thickness direction as shown in FIG. 6, or may not penetrate the second intermediate layer 11 as shown in FIG. 7.
[0039] The second intermediate layer 11 may be thicker than the first intermediate layer 9. The thickness t2 of the second intermediate layer 11 may be, for example, 10 μm or more and 200 μm or less. As shown in FIGS. 5 to 7, the thickness t2 of the second intermediate layer 11 is the thickness of the second intermediate layer 11 located between the first intermediate layer 9 and the first electrode layer 3, and may be said to be the distance between the first intermediate layer 9 and the first electrode layer 3. If the thickness t2 of the second intermediate layer 11 is greater than the thickness t1 of the first intermediate layer 9, Cr contained in the first intermediate layer 9 is less likely to diffuse into the first electrode layer 3.
[0040] When the second intermediate layer 11 has the above open porosity, i.e., an open porosity of 30% or more, the second intermediate layer 11 may fill at least a part of the through-hole 10. That is, the thickness of the second intermediate layer 11 located above the through-hole 10 shown in Fig. 7 may be greater than t2. The thickness of the second intermediate layer 11 located above the through-hole 10 shown in Fig. 7 may be smaller than t2.
[0041] The second intermediate layer 11 may contain second conductive particles. When the second intermediate layer 11 contains the second conductive particles, electricity generated in the element section 6 can be easily collected by the metal plate 2. The second conductive particles contained in the second intermediate layer 11 may be metal or alloy particles, conductive oxide particles, or the like as described above. The material of the second conductive particles contained in the second intermediate layer 11 may be the same as or different from the first conductive particles contained in the first intermediate layer 9 described above.
[0042] The second conductive particles contained in the second intermediate layer 11 may contain a metal element having electrical conductivity in a reduced state. Examples of the metal element having electrical conductivity in a reduced state include Ni, Cu, Co, and Zn. When the first electrode layer 3 is a fuel electrode, the porous second intermediate layer 11 comes into contact with a fuel gas such as a reducing hydrogen-containing gas at high temperatures. Since the second intermediate layer 11 is porous and has a large surface area, the second conductive particles contained in the second intermediate layer 11 are easily reduced in a reducing atmosphere. Since the second conductive particles contained in the second intermediate layer 11 contain a metal element having electrical conductivity in a reduced state, the second intermediate layer 11 can have high electrical conductivity even in a reducing atmosphere, and the electricity generated in the element unit 6 can be easily collected by the metal plate 2.
[0043] The first conductive particles contained in the porous first intermediate layer 9 may also contain a metal element having conductivity in a reduced state. The dense first intermediate layer 9 may contain an oxide as the first conductive particles. Since the dense first intermediate layer 9 has a small surface area, the first conductive particles of an oxide contained in the first intermediate layer 9 are difficult to reduce in a reducing atmosphere.
[0044] The second intermediate layer 11 may further contain an inorganic oxide. Examples of the inorganic oxide contained in the second intermediate layer 11 include oxides of Ti, Zr, Al, Si, Mg, Ca, Sr, Ba, etc., and rare earth oxides of Y, Yb, Ce, Gd, etc. The inorganic oxide contained in the second intermediate layer 11 may be, for example, stabilized zirconia, a rare earth oxide, an ABO3 type perovskite oxide, or titanium oxide. The rare earth oxide includes yttrium oxide (Y2O3).
[0045] When the first electrode layer 3 is an anode, the second intermediate layer 11 may contain stabilized zirconia or a rare earth oxide contained in the anode. When the first electrode layer 3 is an cathode, the second intermediate layer 11 may contain a conductive ABO3-type perovskite oxide contained in the cathode. When the second intermediate layer 11 contains the same inorganic oxide as the inorganic oxide contained in the first electrode layer 3, the adhesive strength between the first electrode layer 3 and the metal plate 2 can be increased.
[0046] The second intermediate layer 11 may contain at least one inorganic oxide of Ti, Al, and Si. When the second intermediate layer 11 contains an inorganic oxide of Ti, Al, or Si, the components of the second conductive particles contained in the second intermediate layer 11 are more likely to dissolve or diffuse into the first intermediate layer 9, the ratio of the first conductive particles contained in the first intermediate layer 9 becomes larger, and the conductivity of the first intermediate layer 9 can be increased.
[0047] When the second intermediate layer 11 contains second conductive particles and an inorganic oxide, the ratio of the second conductive particles may be, for example, 40 mol% or more and 80 mol% or less of the total amount of elements contained in the second intermediate layer 11 converted into oxides, and the ratio of the inorganic oxide may be, for example, greater than 20 mol% and less than 60 mol%.
[0048] The metal plate 2 may have a recess or a protrusion on at least one of the first surface 2a and the second surface 2b. FIG. 8 shows an example of a cell 1 including a metal plate 2 having a recess on the first surface 2a. The upper view of FIG. 8 is a cross-sectional view of the cell 1, and the lower view is a plan view of the first surface 2a of the metal plate 2. As shown in FIG. 8, when the metal plate 2 has a recess on the first surface 2a, the recess may not be in contact with the first electrode layer 3. That is, the metal plate 2 may have a gap between the recess on the first surface 2a and the first electrode layer 3. In this case, the gap between the recess on the first surface 2a and the first electrode layer 3 may be the gas flow path 7. In the cell 1 shown in FIG. 8, the metal plate 2 also serves as the flow path member 8, and the metal plate 2 may not have gas permeability between the first surface 2a and the second surface 2b.
[0049] FIG. 9 shows an example of a cell 1 including a metal plate 2 having a convex portion on the first surface 2a. The upper view of FIG. 9 is a cross-sectional view of the cell 1, and the lower view is a plan view of the first surface 2a of the metal plate 2. When the metal plate 2 has a convex portion on the first surface 2a as shown in FIG. 9, only the convex portion may be in contact with the first electrode layer 3. In such a cell 1, a gap may be formed between the first electrode layer 3 and a portion of the first surface 2a of the metal plate 2 other than the convex portion, and this gap may be used as the gas flow path 7. In the cell 1 shown in FIG. 9, the metal plate 2 also serves as the flow path member 8, and the metal plate 2 may not have gas permeability between the first surface 2a and the second surface 2b.
[0050] The metal plate 2 may have unevenness on both the first surface 2a and the second surface 2b as shown in FIG. 10. The upper view of FIG. 10 is a cross-sectional view of the cell 1, and the lower view is a plan view of the first surface 2a of the metal plate 2. As shown in FIG. 10, the convex portion of the first surface 2a of the metal plate 2 may be in contact with the first electrode layer 3. Such a cell 1 may have a gap between the concave portion of the first surface 2a of the metal plate 2 and the first electrode layer 3, and this gap may be used as the gas flow path 7. In the cell 1 shown in FIG. 10, the metal plate 2 also serves as the flow path member 8, and the metal plate 2 may not have gas permeability between the first surface 2a and the second surface 2b.
[0051] 8 to 10 also has the above-mentioned first intermediate layer 9 between the first surface 2a and the first electrode layer 3. The cell 1 shown in FIGS. 8 to 10 may further have a second intermediate layer 11.
[0052] (Evaluation method) The presence or absence of the first intermediate layer 9 and the second intermediate layer 11 can be confirmed, for example, by observing the cross section of the cell 1 with a scanning electron microscope (SEM), a scanning transmission electron microscope (STEM), or a transmission electron microscope (TEM). The elements and their content ratios contained in the first intermediate layer 9 and the second intermediate layer 11 can be analyzed with, for example, wavelength dispersive X-ray spectroscopy (WDS), energy dispersive X-ray spectroscopy (EDS), or an electron probe microanalyzer (EPMA). From the obtained elemental analysis results, the molar ratios of Cr2O3, the first or second conductive particles, and the inorganic oxide in terms of oxides can be calculated. In addition, if necessary, the first intermediate layer 9 or the second intermediate layer 11 may be cut out from the cell 1 and subjected to elemental analysis such as high-frequency inductively coupled plasma (ICP) emission spectroscopy.
[0053] The volume ratio of the first conductive particles contained in the first intermediate layer 9 or the second conductive particles contained in the second intermediate layer 11 may be calculated based on the calculated molar ratios of Cr2O3, the first or second conductive particles, and the inorganic oxide. The volume ratio of the first conductive particles contained in the first intermediate layer 9 may be determined, for example, by performing element mapping of a cross section of the first intermediate layer 9, calculating the area occupancy of the elements contained in the first conductive particles by image analysis, and converting the area occupancy into a volume ratio. The volume ratio of the second conductive particles contained in the second intermediate layer 11 may be determined by performing image analysis of an element mapping image of a cross section of the second intermediate layer 11.
[0054] (Cell manufacturing method) A method for manufacturing a cell 1 having a first intermediate layer 9 when the first electrode layer 3 is used as the fuel electrode will be described. A base material such as a stainless steel alloy containing Cr is prepared as the metal plate 2. The base material may be an alloy plate or alloy foil. When the metal plate 2 is gas permeable, the base material may be an alloy plate or alloy foil having through holes 10, or may be a porous sintered body of metal powder. In addition, a laminate of a fuel electrode containing Ni and / or NiO and stabilized zirconia, and stabilized zirconia to become the solid electrolyte layer 4 is prepared.
[0055] The laminate of the fuel electrode and the solid electrolyte layer 4 may be produced by the following method. A binder is added to a slurry obtained by mixing Ni or NiO powder and stabilized zirconia powder in an organic solvent, and the slurry is formed into a sheet to obtain a sheet-shaped fuel electrode body. A binder is added to a slurry obtained by mixing stabilized zirconia powder in an organic solvent, and the slurry is formed into a sheet on the sheet-shaped fuel electrode body to obtain a laminate-shaped body. The obtained laminate-shaped body is fired to obtain a laminate of the fuel electrode and the solid electrolyte layer 4.
[0056] The substrate and the fuel electrode, i.e., a laminate of the first electrode layer 3 and the solid electrolyte layer 4, are bonded with an adhesive. As the adhesive, a paste containing conductive particles of at least one of Ni, NiO, Cu, Co, and Zn, and inorganic oxides of at least one of oxides of Ti, Zr, Al, Si, Mg, Ca, Sr, Ba, etc., and rare earth oxides of Y, Yb, etc. is used. The adhesive may contain not only one type of conductive particles but also two or more types of inorganic oxides, and may contain not only one type of inorganic oxide but also two or more types of inorganic oxides. The inorganic oxide may be a composite oxide of two or more elements.
[0057] An adhesive is applied to the first surface 2a of the substrate, and the first surface 2a of the substrate to which the adhesive is applied is bonded to the surface of the first electrode layer 3 of the laminate. The bonded substrate and laminate are heat-treated in a nitrogen atmosphere or in air at a temperature in the range of 1000°C to 1200°C, for example, for 0.5 to 2 hours. After the heat treatment, a Cr2O3 film having first conductive particles such as Ni, Cu, Co, and Zn dispersed therein is formed between the substrate and the first electrode layer 3.
[0058] Furthermore, when heat treatment is performed in a reducing atmosphere, the oxides that make up the fuel electrode are reduced, making it easier for particles of the material contained in the fuel electrode to grow. As a result, sintering of the fuel electrode may progress, making it more difficult for the fuel electrode to react with the fuel gas, and the electrical resistance of the fuel electrode may increase.
[0059] Depending on the type of inorganic oxide contained in the adhesive, the coating thickness of the adhesive, the heat treatment conditions, etc., a second intermediate layer 11 may be formed between the substrate and the first electrode layer 3. The components of the adhesive may diffuse into the substrate or the first electrode layer 3, and a clear second intermediate layer 11 may not be formed. For example, when the coating thickness of the adhesive is 10 μm or more, or when the heat treatment time is short, the components of the adhesive tend not to diffuse into the substrate or the first electrode layer 3 and tend to remain at the interface, and the second intermediate layer 11 is likely to be formed. In addition, when the coating thickness of the adhesive is less than 1 μm, or when the heat treatment time is long, most of the components of the adhesive tend not to diffuse into the substrate or the first electrode layer 3 and tend not to remain at the interface, and a clear second intermediate layer 11 is likely to be formed.
[0060] When the adhesive contains titanium oxide (titania), the melting point of the adhesive decreases, making the adhesive easier to sinter, and the components of the conductive particles more easily dissolve and diffuse into the first intermediate layer 9 and the first electrode layer 3. Furthermore, the Ti element dissolves into the chromium oxide of the first intermediate layer 9, making it possible to further increase the conductivity of the first intermediate layer 9.
[0061] Furthermore, when the adhesive contains any one of titania, aluminum oxide (alumina), and silicon oxide (silica), the thermal expansion coefficient of the adhesive layer, i.e., second intermediate layer 11, is reduced. When first electrode layer 3 is a fuel electrode, the difference between the thermal expansion coefficient of second intermediate layer 11 and the thermal expansion coefficients of metal plate 2 and first electrode layer 3 is reduced, making it difficult for second intermediate layer 11 to peel off from metal plate 2 and first electrode layer 3. Furthermore, these inorganic oxides facilitate the migration of the components of the conductive particles contained in the adhesive to the chromium oxide layer that becomes first intermediate layer 9 on the surface of the substrate.
[0062] When the adhesive simultaneously contains Ni / NiO, titanium oxide (titania), and yttrium oxide, Ni / NiO and titanium oxide (titania) react with yttrium oxide to form a composite oxide such as Y2Ti2O7 or Y2Ti2O7 with NiO in solid solution. The crystal phase of this composite oxide is stable in a reducing atmosphere, the crystal structure is unlikely to change depending on the atmosphere, and destruction due to volume change accompanying the phase transformation of the crystal is unlikely to occur.
[0063] The cell 1 of the present disclosure can be obtained by forming an air electrode, which is the second electrode layer 5, on the surface of the solid electrolyte layer 4 of the substrate and laminate joined with an adhesive. The air electrode may be formed by adding a binder to a slurry in which, for example, conductive ABO3-type perovskite oxide powder is mixed in an organic solvent, printing the slurry on the surface of the solid electrolyte layer 4, and then firing the substrate and laminate in an oxidizing atmosphere at 1000°C to 1200°C.
[0064] In the above-mentioned manufacturing method, a laminate of the first electrode layer 3 and the solid electrolyte layer 4 is prepared in advance, and then the laminate is bonded to the substrate. However, the first electrode layer 3 and the solid electrolyte layer 4 may be sequentially formed on the metal plate 2 without preparing a laminate of the first electrode layer 3 and the solid electrolyte layer 4 in advance. For example, a sheet molded body to become the first electrode layer 3 may be attached to the metal plate 2 to which an adhesive is applied, and a sheet to become the solid electrolyte layer 4 may be further formed on the sheet molded body and then fired. After firing the metal plate 2 and the first electrode layer 3 bonded with the adhesive, the solid electrolyte layer 4 may be formed on the surface of the fired first electrode layer 3 by a vacuum film formation method such as PVD.
[0065] (Cell stack device) 11, the cell stack device 20 includes a cell stack 21 in which a plurality of cells 1 are arranged, and a gas tank 22. The lower end of the cell 1 is joined and fixed to the opening of the gas tank 22. The gas tank 22 supplies fuel gas to the plurality of cells 1.
[0066] The cell stack 21 includes a plurality of cells 1 arranged or stacked in the thickness direction of the cells 1, and a conductive member 23a that electrically connects adjacent cells 1 in series. The cells 1 have the above-mentioned first intermediate layer 9. The direction in which the plurality of cells 1 are arranged is referred to as the arrangement direction x.
[0067] The conductive members 23a may also be disposed at both ends of the cell stack 21 in the arrangement direction x. The conductive members 23a may be bonded to the cells 1 with a conductive adhesive. The material of the conductive members 23a may be an elastic metal or alloy, or a metal fiber or alloy fiber felt. The metal fiber or alloy fiber felt may be surface-treated as necessary.
[0068] 11, the cell stack device 20 includes an end conductive member 23b on the outside of the arrangement direction x of the cell stack 21. The end conductive member 23b is electrically connected to the cell 1 located on the outermost side in the arrangement direction x. The end conductive member 23b has an extraction portion 23c that protrudes outward in the arrangement direction x. The extraction portion 23c collects electricity generated by the cells 1 and extracts it to the outside.
[0069] Fig. 12 is an enlarged cross-sectional view of the dashed line portion in Fig. 11. The lower end of the cell 1 is fixed to the opening of the gas tank 22 with a sealant S as shown in Fig. 12. The gas flow path 7 of the cell 1 communicates with a fuel gas chamber (not shown) of the gas tank 22. The material of the sealant S may be, for example, glass having excellent heat resistance.
[0070] The lower ends of the conductive member 23a and the end conductive member 23b may be fixed to the gas tank 22 by a seal material S. The end conductive member 23b may be integrated with the cell stack 21.
[0071] (Module) FIG. 13 is an external perspective view showing an example of a module including a cell stack device.
[0072] The module 30 includes a rectangular parallelepiped storage container 31 and the above-mentioned cell stack device 20 stored inside the storage container 31. A reformer 32 is disposed above the cell stack 21. The reformer 32 is connected to the gas tank 22 by a gas circulation pipe 33. The reformer 32 reforms raw fuel, such as natural gas or kerosene, supplied from a raw fuel supply pipe 34 to generate fuel gas. The gas circulation pipe 33 supplies the fuel gas reformed by the reformer 32 to the gas tank 22. The fuel gas is supplied from the gas tank 22 to the gas flow path 7 of the cell 1.
[0073] 13 shows a state in which the front and rear parts, which are part of the storage container 31, have been removed and the cell stack device 20 housed inside the storage container 31 has been taken out to the rear. The module 30 shown in FIG. 13 allows the cell stack device 20 to be housed by sliding it into the storage container 31. The cell stack device 20 does not need to include the reformer 32.
[0074] The storage container 31 is provided with an oxygen-containing gas introduction member 35 therein. The oxygen-containing gas introduction member 35 in FIG. 13 is disposed between the two cell stacks 21 in a state in which the cell stack device 20 is accommodated in the storage container 31. The oxygen-containing gas introduction member 35 supplies oxygen-containing gas to the lower end of the cell 1. The oxygen-containing gas flows from the lower end to the upper end of the cell 1 by the oxygen-containing gas introduction member 35 in accordance with the flow of the fuel gas. The fuel gas discharged from the gas flow path 7 of the cell 1 to the upper end of the cell 1 is mixed with the oxygen-containing gas and combusted. The temperature of the cell 1 is increased by the combustion of the fuel gas discharged at the upper end of the cell 1, and the start-up of the cell stack device 20 can be accelerated. In addition, the combustion of the fuel gas at the upper end of the cell 1 warms the reformer 32 disposed above the cell 1, and the reforming reaction can be efficiently carried out in the reformer 32.
[0075] (Module housing device) Fig. 14 is an exploded perspective view showing an example of a module housing device. Note that some components are omitted in Fig. 14. The module housing device includes an outer case, a module housed in the outer case, and an auxiliary device that operates the module.
[0076] The module accommodating device 40 shown in Fig. 14 has support posts 41 and an exterior plate 42. A partition plate 43 divides the interior of the exterior case into upper and lower sections. The space above the partition plate 43 in the exterior case is a module accommodating chamber 44 that accommodates the module 30, and the space below the partition plate 43 in the exterior case is an auxiliary equipment accommodating chamber 45 that accommodates the auxiliary equipment that operates the module 30. Note that a description of the auxiliary equipment accommodated in the auxiliary equipment accommodating chamber 45 is omitted.
[0077] The partition plate 43 has an air flow port 46 for allowing air from the auxiliary equipment housing chamber 45 to flow toward the module housing chamber 44. A part of the exterior plate 42 that forms the module housing chamber 44 has an exhaust port 47 for exhausting air from within the module housing chamber 44. The air from within the module housing chamber 44 is exhausted from the exhaust port 47.
[0078] Since the module housing device 40 includes the above-mentioned module 30 in the module housing chamber 44, the module housing device 40 can have high power generation efficiency.
[0079] Although the present disclosure has been described in detail above, the present disclosure is not limited to the above-described embodiments. Various modifications and improvements can be made to the cell, cell stack device, module, and module housing device of the present disclosure without departing from the gist of the present disclosure.
[0080] For example, in the above-mentioned cell stack device 20, an example is shown in which fuel gas is supplied to the gas flow path 7 inside the cell 1 and an oxygen-containing gas is supplied to the outside of the cell 1, but it is also possible to supply oxygen-containing gas to the gas flow path 7 and supply fuel gas to the outside of the cell 1.
[0081] In addition, in the above explanation, a fuel cell, a fuel cell stack device, a fuel cell module, and a fuel cell device are given as examples of a "cell," a "cell stack device," a "module," and a "module containing device," but other examples may be an electrolytic cell, an electrolytic cell stack device, an electrolytic module, and an electrolytic device, respectively. EXAMPLES
[0082] A 0.3 mm thick stainless steel alloy plate containing Cr was drilled with 81 through holes per cm. 2A substrate was prepared on which the NiO and stabilized zirconia were formed. A laminate was also prepared consisting of an anode, which was a mixture of NiO and stabilized zirconia, and a solid electrolyte layer of stabilized zirconia. The anode contained 60 mass% NiO and 40 mass% stabilized zirconia. The stabilized zirconia in the anode and solid electrolyte layer contained 8 mol% yttrium in terms of Y2O3. The laminate was integrated by firing in air at a maximum temperature of 1400°C for 2 hours.
[0083] As an adhesive, a material was prepared by adding TiO2 powder and Y2O3 powder instead of the stabilized zirconia of the fuel electrode, that is, material A containing NiO, TiO2, and Y2O3. The composition of material A was 65 mass% NiO, 10 mass% TiO2, and 25 mass% Y2O3.
[0084] A paste of material A was prepared and applied to the surface of a stainless steel alloy substrate. The thickness of the adhesive applied was 50 μm. The adhesive-coated surface of the substrate was bonded to the fuel electrode surface of the laminate, and then heat treatment was performed in air at a maximum temperature of 1050°C for 2 hours to bond the substrate and the fuel electrode, obtaining a bonded body.
[0085] The electrical resistivity of the resulting assembly was measured as follows. LaSrCoO3 was baked onto the solid electrolyte layer to form an electrode with a diameter of 10 mm. A platinum mesh was attached to the surface of the substrate facing this electrode, i.e., the surface not having the power generating element, to form a counter electrode. The electrical resistivity was measured by an AC four-terminal method.
[0086] As a comparative example, the electrical resistivity of a substrate that was heat-treated under the same conditions without applying an adhesive was measured. The electrical resistivity of the comparative example was 7.06 Ω m, while the electrical resistivity of the entire intermediate layer, including the first and second intermediate layers of the bonded body using material A, was 0.047 Ω m.
[0087] The cross sections of the comparative example and the bonded body using material A were observed with a scanning electron microscope (SEM). The cross sections of each sample were analyzed using energy dispersive X-ray spectroscopy (EDS). In the backscattered electron image of the SEM, a dense chromium oxide layer with a contrast different from that of metal was formed on the surface of the substrate of the comparative example, and particles containing other elements, i.e., first conductive particles, were not detected in the chromium oxide layer. Both of the bonded bodies using material A or material B had a first intermediate layer containing chromium oxide and first conductive particles containing Ni, and a second intermediate layer containing porous second conductive particles containing Ni and inorganic oxides such as zirconia, TiO2, and Y2O3 between the substrate and the fuel electrode.
[0088] The first intermediate layer of the bonded body using material A had an average thickness of 6 μm and contained 80 mol % of chromium oxide and 20 mol % of Ni and Ti calculated as oxides. The second intermediate layer had an average thickness of 50 μm, an open porosity of 40%, and contained 30 mol % of Ti and Y calculated as oxides and 70 mol % of Ni calculated as oxides. [Explanation of symbols]
[0089] 1: Cell 2: Metal plate 3: First electrode layer 4: Solid electrolyte layer 5: Second electrode layer 6: Element section 7: Gas flow path 8: Flow path material 9: First middle layer 10:Through hole 11: Second middle tier 20: Cell stack device 21: Cell Stack 22: Gas tank 30: Module 31: Containment Container 32: Reformer 33: Gas distribution pipe 40: Module storage device
Claims
1. A cell which is a solid oxide fuel cell or electrolysis cell, comprising: A metal body which is a dense plate or a porous sintered body containing Cr and has a pair of opposing first and second surfaces; The metal body is located on the surface thereof, has gas permeability, and is made of Cr. 2 O 3 A first film comprising: a porous second film located on a surface of the first film and containing an inorganic oxide of at least one of Ti, Al, and Si; an element portion disposed on the first surface and having a first electrode layer that is an anode, a solid electrolyte layer located on the first electrode layer, and a second electrode layer located on the solid electrolyte layer; When the metal body is a dense plate, it has through holes opening on the first surface and the second surface, or a concave portion or a convex portion facing at least the first surface, The first film is made of Cr. 2 O 3 and a first conductive particle different from the second film includes second conductive particles; the first film is located on at least the first surface; The first membrane and the second membrane are located between the first surface and the first electrode layer.
2. The particle size of the first conductive particles is smaller than the thickness of the first film. The cell of claim 1 .
3. The first conductive particles include metal or alloy particles. The cell of claim 1 .
4. A cell which is a solid oxide fuel cell or electrolysis cell, comprising: A metal body which is a dense plate or a porous sintered body containing Cr and has a pair of opposing first and second surfaces; The metal body is located on the surface thereof, has gas permeability, and is made of Cr. 2 O 3 A first film comprising: a porous second film located on a surface of the first film and having a composition different from that of the first film; an element portion disposed on the first surface and having a first electrode layer that is an anode, a solid electrolyte layer located on the first electrode layer, and a second electrode layer located on the solid electrolyte layer; When the metal body is a dense plate, it has through holes opening on the first surface and the second surface, or a concave portion or a convex portion facing at least the first surface, The first film is made of Cr. 2 O 3 and a first conductive particle different from The first conductive particles are LaCrO 3 system or LaSrTiO 3 Perovskite oxides of the system, the first film is located on at least the first surface; The first membrane and the second membrane are located between the first surface and the first electrode layer.
5. A cell stack device comprising a cell stack in which the cell according to any one of claims 1 to 4 is arranged.
6. A module comprising: a container; and the cell stack device according to claim 5 housed in the container.
7. A module housing device comprising: an outer case; and the module according to claim 6 and an auxiliary device for operating the module, both housed within the outer case.
Citation Information
Patent Citations
Solid electrolyte type fuel cell
JP1998172590A
Solid oxide type fuel battery
JP2015122224A
Metal support sofc
JP2016115506A
Fuel battery member and manufacturing method for the same
JP2016195101A
Cell stack device, module and module housing device
JP2017112045A